Ionizing radiation impact on the mechanical properties of a wood-plastic composite: a review - Harun, Siti Nur Idayu; Othman, Siti Amira (Asian Scholars Network, 2020)
This paper reviews the effect of radiation on the mechanical properties of WPC. WPC can be defined as mixture of wood in a polymer matrix. Composite that used in this research mainly consists of 40% polyethylene (PE), 50 % wood fiber and the rest is carbon black. The WPC were then irradiated and go through post extrusion process under required dose levels of 0, 50, 100, 150, 200 and 250 kGy with the aid of the electron beam treatment (EB). Soon after, the irradiated WPC then classified using a test called bending test which specify in third point bending test (ASTM D4761) along with scanning electron microscopy (SEM). It was checked that two factors are affected with the increasing dose level and they were ultimate strength and modulus of elasticity (MOE). Diagnosis on the morphology of polyethylene by the research found that there was significant difference between the radiated and irradiated surfaces.